PENGARUH PERLAKUAN ASAP CAIR TERHADAP SIFAT SENSORIS DAN MIKROSTRUKTUR SOSIS ASAP IKAN LELE DUMBO (Clarias gariepinus) - E Ernawati (Jurnal Kelautan, 2015)
Research was conducted on the effects of the treatment liquid smoke sensory properties and microstructure of fish smoked sausage catfish (Clarias gariepinus). Research using randomized block design (RAK) the treated liquid smoke concentration and length of immersion in liquid smoke. Chemical analysis includes the measurement of water content, protein content, fat content and phenol. Organoleptic analysis includes taste, flavor, color and texture using preference level (Hedonic Scale). The results obtained showed that the catfish fish sausage liquid smoke concentration of 20% and 30 minutes immersion time is best treated with a score of 0.67, and 62.56 on the analysis of water content, fat content 12.33 ± 0.61%, and phenol 292.74 ppm. Penetration of liquid smoke clearly visible on the microstructure of smoked sausage, both on the best treatment sausage and smoked sausage commercial. Overall penetration is formed on the surface of the sausage and closing most of its surface, forming a layer on the surface of the sausage. 2.500x magnification SEM microstructure shows that the best smoked sausage has a structure of emulsion more evenly with globules are smaller and smoother than smokeless and smoked sausage commercial.Key Words: catfish, liquid smoke, scanning electron microscope